Sulfadiazine Salicylaldehyde-Based Schiff Bases: Synthesis, Antimicrobial Activity and Cytotoxicity - Krátký, Martin; Dzurková, Magdaléna; Janoušek, Jiří; Konečná, Klára; Trejtnar, František; Stolaříková, Jiřina; Vinšová, Jarmila (Molecules (Basel, Switzerland), 2017)
The resistance among microbes has brought an urgent need for new drugs. Thus, we synthesized a series of Schiff bases derived from the sulfa drug sulfadiazine and various salicylaldehydes. The resulting 4-[(2-hydroxybenzylidene)amino]-N-(pyrimidin-2-yl)benzene-sulfonamides were characterized and evaluated against Gram-positive and Gram-negative bacteria, yeasts, moulds, Mycobacterium tuberculosis, nontuberculous mycobacteria (M. kansasii, M. avium) and their cytotoxicity was determined. Among bacteria, the genus Staphylococcus, including methicillin-resistant S. aureus, showed the highest susceptibility, with minimum inhibitory concentration values from 7.81 µM. The growth of Candida sp. and Trichophyton interdigitale was inhibited at concentrations starting from 1.95 µM. 4-[(2,5-Dihydroxybenzylidene)amino]-N-(pyrimidin-2-yl)-benzenesulfonamide was identified as the most selective Schiff base for these strains with no apparent cytotoxicity and a selectivity index higher than 16. With respect to M. tuberculosis and M. kansasii that were inhibited within the range of 8 to 250 µM, unsubstituted 4-[(2-hydroxy-benzylidene)amino]-N-(pyrimidin-2-yl)benzenesulfonamide meets the selectivity requirement. In general, dihalogenation of the salicylic moiety improved the antibacterial and antifungal activity but also increased the cytotoxicity, especially with an increasing atomic mass. Some derivatives offer more advantageous properties than the parent sulfadiazine, thus constituting promising hits for further antimicrobial drug development.
Keywords: Hep G2 Cells; Antifungal Agents; pyrimidiny; Schiff Bases; buňky Hep G2; mikrobiální testy citlivosti; Schiff bases; cytotoxicity; sulfadiazine; sulfonamides; antimycobacterial activity; Structure-Activity Relationship; lidé; antiinfekční látky; Anti-Infective Agents; Anti-Bacterial Agents; sulfadiazin; Sulfadiazine; antibacterial activity; Aldehydes; antifungal activity; Microbial Sensitivity Tests; aldehydy; Schiffovy báze; vztahy mezi strukturou a aktivitou; Cell Survival; viabilita buněk; antibakteriální látky; antifungální látky; Pyrimidines; Humans